EVALUASI MANAJEMEN PERALATAN MEDIS BERDASAR STANDAR KESELAMATAN & KESEHATAN KERJA Di RSUD Dr. ACHMAD DARWIS KABUPATEN LIMA PULUH KOTA - , Zainul Asmi, DR. Ir. Widodo Hariyono, A.Md., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : management of medical instrumentation is very important to execute with based on standard of occupational safety and health, to found out the proper medical instrumentation, safety to operator, patient, and to get long lasting period of medical instrumentation. The aim of this study is how to know the implementation of medical instrumentation building on occupational safety and health aspect begin from planning, placement, maintenance, amelioration, and calibration by Dr. Achmad Darwis Hospital, regency of Lima Puluh Kota. Method : This study using qualitative method with case study to describe or explain the situation, appreciating, and understand about the implementation of medical instrumentation management building on occupational safety and health aspect. Thecnique of collecting data using In Depth Interview, document study, instrumentation picture, dan direct observation. Result : The result of this study point out that in medical instrumentation management, planning step have engaged some of elements such as clinical officer, operator, and technician. In placement of instrumentation which have mobile and portable characteristic is not based on settled standard. Minor maintenance that responsible by operator have not done yet maximally. There are obstacles in amelioration, sparepart, human source, documentation of feature and infrastructure. Conclusion : management of medical instrumentation in RSUD dr. Achmad Darwis have not done yet maximal, mainly in placement and maintenance of instrumentation which have mobile and portable characteristic so it can affect the early broken of instrumentation and not fill occupational safety and health aspect of medical instrumentation maximally.